Decolorization of Methyl Red and Phenol Red By Bacillus subtilis strain BUU005 - นิ่มรัตน์, สุบัณฑิต; ชลศรานนท์, ภาพสุภา; สุขสวัสดิ์, ตรีรัตน์; บุญไทย, ไตรมาศ; วุฒิพันธุ์ชัย, วีรพงศ์ (KKU Science Journal, 2013)
Currently, synthetic dyes play an important role in industries. A variety of synthetic dyes have been used widely in many industries such as azo dye and triphenylmethane dye. Consequently, wastewaters contaminated with these dyes are discharged into environment leading to emergence of environmental problems and health concerns due to carcinogenic potentials of some synthetic dyes and their metabolites. Therefore, this study aimed to determine the effectiveness of Bacillus subtilis strain BUU005 on decolorization of methyl red and phenol red under static condition. Result showed that B. subtilis strain BUU005 was able to decolorize methyl red at 0.1 mM within 35 days of the experiment for 93.38 2.29% of decolorization. However, this bacterium removed partial phenol red which showed percentage of decolorization for 50.62 2.25% at 60th day of the experiment. Indeed, B. subtilis strain BUU005 had probable potential to develop and apply for removal of wastewater containing azo dye.